Digitalization and Circular Economy: Analysis of the Role and Strategy of Culinary Sector MSMEs in Salahutu District Villages - Matruty, Dinatonia Jovery; Faisal, Muhammad (Jurnal Ilmiah Multidisiplin Indonesia (JIM-ID), 2025)
This study aims to examine the influence of digitalization roles and strategies on the implementation of circular economy practices in micro, small, and medium enterprises (MSMEs) within the culinary sector in Tulehu Village, Salahutu District, Central Maluku. Using a quantitative approach, data were collected from 100 MSME actors through structured questionnaires and interviews, and analyzed using multiple linear regression with SPSS. The results show that the role of digitalization has a positive and significant effect on circular economy practices (β= 0.2965, p < 0.001), while digitalization strategies demonstrated an even greater positive and significant effect (β= 0.4205, p < 0.001). Together, these two variables explain 92.3% of the variance in circular economy practices, indicating a strong predictive capability. The findings confirm that technology adoption not only improves operational efficiency but also facilitates sustainable business models in line with the principles of reduce, reuse, recycle, and recovery. Strategically planned digitalization is more effective than technology adoption alone in promoting sustainability. This study contributes to the literature by integrating digital transformation with circular economy practices in the context of island-based MSMEs, and provides practical implications for policymakers and business actors in fostering sustainable local economic development.